Stop stabbing yourself in the back - "Briles, Judith" (Delhi, 2007)
The book was conceptualized when the author was researching and writing Gender Traps. During his research, the author realized that self-sabotage was frequently reported. Thus he got an idea to write this book which identifies 21 self-sabotaging methods and delivers practical solutions and tips to eradicate ones inner traps and self-sabotaging techniques forever. The author delivers practical, realistic and useable steps to delete destructive personal and career-blocking behaviour.
Keywords: Personal improvement